2017
DOI: 10.1245/s10434-017-6085-y
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Biology Predicts Pathologic Complete Response to Neoadjuvant Chemotherapy in Patients Presenting with Locally Advanced Breast Cancer

Abstract: Background Neoadjuvant chemotherapy (NAC) is used to convert patients with inoperable locally advanced breast cancer (LABC) to operability, but has not traditionally been used to avoid mastectomy or axillary dissection in this subset. The purpose of this study was to determine rates of pathologic complete response (pCR) in LABC patients and identify factors predictive of pCR to determine if responding patients might be suitable for limited surgery. Methods From 2006-2016, 1522 patients received NAC followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 20 publications
5
43
2
1
Order By: Relevance
“…On multivariate analysis, receptor subtype remained the only significant predictor of overall pCR ( P = 0.02). In line with recent reports the highest pCR rates in our series were achieved in Her2+ and TN tumors (59.5% and 29% respectively). In light of the impact of tumor subtype on the achievement of pCR, the need for breast surgery is being questioned in Her2+ and TN tumors, when a post NAC biopsy indicates a breast pCR, and clinical trials are currently ongoing, in which breast surgery is omitted in patients with these tumor subtypes and documented breast pCR .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…On multivariate analysis, receptor subtype remained the only significant predictor of overall pCR ( P = 0.02). In line with recent reports the highest pCR rates in our series were achieved in Her2+ and TN tumors (59.5% and 29% respectively). In light of the impact of tumor subtype on the achievement of pCR, the need for breast surgery is being questioned in Her2+ and TN tumors, when a post NAC biopsy indicates a breast pCR, and clinical trials are currently ongoing, in which breast surgery is omitted in patients with these tumor subtypes and documented breast pCR .…”
Section: Discussionsupporting
confidence: 93%
“…We confirm a correlation between BC subtypes and axillary pCR in a consecutive series of cN+ patients who received NAC and surgery at our Institutions. Overall pCR was achieved in almost one third of patients, in line with recent reports . Luminal A tumors never achieved a pCR.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The research of our center22 found that the rates of axillary lymph node pCR (apCR) after NAC in clinically node positive (cN + ) patients with HER2+ (with targeted therapy) and TN were 58.6% and 53.2%, respectively, which were significantly higher than that in HR+/HER2− patients (21.2%, P < 0.001). Gentile et al23 and Kantor et al 24 also reached the same results. According to apCR situation in cN + patients, we deduced that ALNs occult metastasis had lower ypN0 after NAC in the initial cN0 patients with HR+/HER2− subtype than those with TN and HER2+ (with targeted therapy) subtypes.…”
mentioning
confidence: 57%